The Investigation of Savonius Type and Darrieus H Type Wind Turbine Simulation with Wind Speed Variable - Wibby Aditya Putra Utama; Yohandri Bow; M. Syahirman Yusi (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2021)
The demand for electrical energy that continues to increase along with the advancement of civilization and also the increasing number of people as well as the reduced level of fulfillment and availability of non-renewable energy sources, it is necessary to have renewable energy resources that capable of fulfill these energy demand in a more environmental friendly. One of the natural energies that we can use is wind energy, which is easy to get and lasts continuously. This research examines the comparison of the power generated from the vertical axis wind turbine savonius type and darrieus H type. The wind that use in this research get from from the fan. The test is doing by varying the wind speed by adjusting the fan speed. The fan is directed to the wind turbine to rotate the wind turbine. To measure the wind speed produced by the fan, a digital anemometer is used. The result of this research is the relation data of voltage to rpm and voltage to wind speed of wind turbine.